Preparation of different biochars and their adsorption performance for heavy metals and antibiotics - DENG Zhihua; LIU Rui; LI Biqing (Gongye shui chuli)
Coffee grounds, walnut shells, water hyacinth and coconut shells were used as raw materials to prepare biochars at different pyrolysis temperatures, and the simulated wastewater containing Cu, Zn, OTC, CIP, and DOX was purified. The results showed that 700 ℃ was the optimal pyrolysis temperature for biochar, and water hyacinth biochar(SBC700) had the best adsorption effect on single heavy metal Cu and Zn. Coconut shell biochar(YBC700) had a strong adsorption effect on single antibiotic OTC, CIP, and DOX. The adsorption behaviors of four biochars on single heavy metal and antibiotic were chemical adsorption. Composite biochar was prepared from SBC and YBC at 700 ℃, and its adsorption effect on Cu, Zn and one antibiotic compound contaminant was studied. Composite biochar was beneficial for enhancing the adsorption efficiecy of Cu and antibiotics in compound contaminant systems. The longer the residence time, the better the removal effect of composite biochar on Cu and Zn, and the effect on three antibiotics was no significant. Considering the economic benefits and removal effects, the optimal dosage of composite biochar was 2.5 g/L. The adsorption capacity of biochar for Cu and Zn also increased gradually with the increase of pH, which was 1.90 mg/g and 8.40 mg/g at pH 6, respectively. There was no significant change in the adsorption capacity of biochar for OTC, CIP, and DOX, and the average removal rates were higher than 88%. The water hyacinth and coconut shell composite biochar prepared at the pyrolysis temperature of 700 ℃ had the best comprehensive properties, which provided a new idea for the adsorption of heavy metals and antibiotic compound pollution.